Negative Stereotypes Towards Older People. A Study with Teachers in Initial Training - Pilar Moreno-Crespo; Olga Moreno-Fernández; Encarnación Pedrero-García (Universidad Nacional, Costa Rica, 2022)
Objective. To describe whether there are stereotypes towards older adults by the group of teachers in initial training. Method. The approach was quantitative and not probabilistic through a statistical study with university students preparing to become primary school teachers in the Spanish education system. This training profile includes adult and senior education as an additional professional opportunity. The sample (n=110) has been selected among students of the Primary Education Degree. We have applied the Negative Stereotype Questionnaire for the Elderly (CENVE) and the Educational Stereotype Questionnaire for the Elderly (CEEAM). Results. We suggest that the respondents present some degree of stereotypes towards older adults; the stereotype is greater when we question the deterioration of memory and cognitive impairment in general. However, the data are positive, except that in the case of the health factor we found two items in which respondents reported a higher level of stereotyping. Conclusions. Based on these results, we conclude that it is necessary to work on stereotypical perceptions, especially with students pursuing careers related to education, since their professional performance can lead them to develop their teaching careers in adult and senior education. The education professions must be involved in improving quality of life, active aging, and lifelong learning through professional practice and the elimination of personal and societal stereotypes.